(untitled) (Global Journal of Science Frontier Research, 2018)
This is an approach to determine the residual amounts of pesticides with various activities present in environmental samples by applying electro chemical technique adsorptive stripping voltammetry. Average amounts for ten replicates founded by using carbon nano tubes paste electrodes as working electrodes. statistical concepts such as standard deviation and correlation coefficient and in all the findings in this approach all the possible errors are minimised and accuracy is maximised. Water samples of various areas are collected and investigated for pesticide residues before and after the application of pesticides.